The purification step is not crucial in EIA measurements of thromboxane B2 and 11-dehydrothromboxane B2 in human plasma - Sadilkova, Lenka; Paluch, Zoltan; Mottlova, Jirina; Bednar, Frantisek; Alusik, Stefan (Clinical laboratory, 2012)
BACKGROUND: Thromboxane B2 (TxB2) and particularly 11-dehydrothromboxane B2 (11-dTxB2) are widely used as prognostic risk markers of platelet activation in cardiovascular diseases. The main errors in TxB2 and 11-dTxB2 determination include either low concentrations of circulating TxB2 (1 - 2 pg/mL) and 11-dTxB2 (0.9 - 4.3 pg/mL) or rather high transiency (mean TxB2 half-life is approximately 5 minutes) as well as an incorrect pre-analytical phase set up. The aim of this study was to investigate the impact of a widely used purification step on the results of enzyme immunosorbent assay (EIA)--based measurement of the two selected thromboxanes. METHODS: For the purpose of this study, 20 plasma samples (10 healthy donors, 10 patients under treatment with acetylsalicylic acid) were screened for TxB2 and 11-dTxB2 concentrations using commercial competitive EIA kits (Cayman Chemicals, Tallinn, Estonia; Neogen, Lexington, KY, USA) with or without the introduction of the purification procedure. RESULTS: The purification step does not significantly affect the results of EIA measurements of the two of TxA2 metabolites (TxB2, 11-dTxB2) in human plasma. The levels of TxB2 and 11-dTxB2 determined in the plasma samples were not significantly changed (p < 0.05) when the purification step was omitted compared to the purified samples. CONCLUSIONS: This study establishes a protocol allowing for reliable and reproducible plasma TxB2 and 11-dTxB2 EIA measurement for routine basic screening of platelet function.
Keywords: reagenční diagnostické soupravy; kardiovaskulární nemoci; Humans; Thromboxane B2; Platelet Activation; Immunoenzyme Techniques; extrakce na pevné fázi; trombocyty; thromboxan B2; lidé; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; reprodukovatelnost výsledků; imunoenzymatické techniky; Blood Platelets; Cardiovascular Diseases; Reproducibility of Results; prognóza; aktivace trombocytů; Aspirin; Solid Phase Extraction; Reagent Kits, Diagnostic; Prognosis